2014
DOI: 10.1186/s40529-014-0072-4
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of microsatellites in the vulnerable orchid Gastrodia flavilabella: the development of microsatellite markers, and cross-species amplification in Gastrodia

Abstract: BackgroundGastrodia flabilabella is a mycoheterotrophic orchid that obtains carbohydrates and nutrients from its symbiotic mycorrhizal fungi. The species is an endemic and vulnerable species enlisted in the “A Preliminary Red List of Taiwanese Vascular Plants” according to the IUCN Red List Categories and Criteria Version 3.1. G. flabilabella dwells the underground of broadleaf and coniferous forest with richness litter. Based on herbarium records, this species is distributed in central Taiwan. Twenty eight mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 25 publications
2
14
0
Order By: Relevance
“…SSRs were used as DNA barcodes to clear identify 5 genotypes of Solanum melongena L. by Chinnappareddy et al [45]. In Orchidaceae, SSR markers were developed and utilized as identification tools in various studies [18,[46][47][48] due to their high reproducibility and variability [45,49,50]. In particular, SSRs in the chloroplast genome were reported to have a high level of polymorphism among species and loci [51].…”
Section: Repeat and Microsatellite Analysismentioning
confidence: 99%
“…SSRs were used as DNA barcodes to clear identify 5 genotypes of Solanum melongena L. by Chinnappareddy et al [45]. In Orchidaceae, SSR markers were developed and utilized as identification tools in various studies [18,[46][47][48] due to their high reproducibility and variability [45,49,50]. In particular, SSRs in the chloroplast genome were reported to have a high level of polymorphism among species and loci [51].…”
Section: Repeat and Microsatellite Analysismentioning
confidence: 99%
“…However, high transferability of microsatellite markers and allele difference are not always compatible. It is common for amplification to fail in several loci in cross-amplification tests (e.g., G. flavilabella and its related species, Tsai et al, 2014), and even if amplified well, similar-sized alleles are observed among taxa (e.g., Livistona rigida and its related species, Kaneko et al, 2011;Stachyurus macrocarpus var. macrocarpus and var.…”
Section: Abstract: Cross Amplification Genetic Variation Inbreedinmentioning
confidence: 99%
“…Microsatellite loci were isolated using the modified AFLP and magnetic bead enrichment method (Ho et al, 2014;Tsai et al, 2014). Genomic DNA from S. samarangense 'Pink' was digested using MseI (Promega, Madison, Wisconsin, USA) and separated by 1.2% agarose gel electrophoresis using a Tris-boric acid-EDTA buffer system.…”
Section: Cloning and Sequencing Of Ssr Locimentioning
confidence: 99%